Role of Intellectual Property in Transferring Pharmaceutical and Medical Innovations: From Development to Use - T. V. Semenova (Регуляторные исследования и экспертиза лекарственных средств)
The key mission of medical science is the development of advanced technologies and the implementation of innovations that protect and improve the health of the population. Tackling this challenge requires providing comprehensive support to developers throughout the lifecycle of their innovative products. It is the cooperation of the scientific community, government agencies, and business stakeholders that will smooth the path of medical innovations from the laboratory workbench to the individual patient. In this interview, Tatiana V. Semenova, Deputy Minister of Health of the Russian Federation, describes the most effective support and guidance measures for promising projects in medicine.